2016
DOI: 10.1111/1751-2980.12350
|View full text |Cite
|
Sign up to set email alerts
|

Diverticulitis: does age matter?

Abstract: The clinical presentation of acute diverticulitis does not seem to be worse in the young population. Younger patients tend to have a more severe presentation on CT scan and more readmissions, but this did not translate to a more severe disease course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 24 publications
2
13
1
3
Order By: Relevance
“…This is in contrast to other studies which show the rate per 100,000 ED visits did not increase significantly among the younger population [8,13,22]. Our study also found that the younger age group had the lowest rate of bowel surgeries of all age groups, which contrasts other studies suggesting that the younger age group may have more severe disease and more likely to require immediate surgical intervention due to complications [10,21,23]. …”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to other studies which show the rate per 100,000 ED visits did not increase significantly among the younger population [8,13,22]. Our study also found that the younger age group had the lowest rate of bowel surgeries of all age groups, which contrasts other studies suggesting that the younger age group may have more severe disease and more likely to require immediate surgical intervention due to complications [10,21,23]. …”
Section: Discussioncontrasting
confidence: 99%
“…The development of acute diverticulitis is associated with obesity, smoking, diet, lack of physical activity, and the use of nonsteroidal anti-inflammatory drugs [9]. Younger individuals with diverticulitis tend to have similar or less severe disease, though they tend to be re-admitted more frequently [8,10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…15 Similar findings were observed in an Israeli cohort; although younger patients were more likely to have extraluminal air on CT, the intraoperative Hinchey score and the need for emergency or multiple surgeries did not differ between the older and younger groups. 16 There were no differences in disease complexity, peritonitis, laboratory findings, and presence of fistula or abscess among older (> 50 years) and younger patients. Younger patients were more likely to have readmissions or diverticular complications, possibly due to their earlier discharge compared with those > 50 years of age.…”
Section: Risk Factors Agementioning
confidence: 81%
“…13,14 Historically, elective resection was recommended after the first attack of complicated diverticulitis in those under the age of 40 due to the belief that young patients with diverticulitis have more aggressive pathology. 15,16 Recent work has challenged this view, however. 14,15,17,18 In a retrospective review of all abdominopelvic computed tomography (CT) scans in those with diverticulitis over a 5-year period in a single institution, young patients (age 50 years) were more likely to be male, have extraluminal air, and have greater colonic wall thickness.…”
Section: Risk Factors Agementioning
confidence: 99%
“…Studies that included more than 20% right-sided diverticulitis were excluded. Studies that did not quantify the number of right-sided diverticulitis patients but were from Western origin were not excluded under the assumption that in the Western world the vast majority of cases (usually above 90% [ 12 14 ]) concern left-sided diverticulitis. Reviews, letters, and case reports were excluded.…”
Section: Methodsmentioning
confidence: 99%